2011 IEEE International Conference on Systems, Man, and Cybernetics 2011
DOI: 10.1109/icsmc.2011.6084140
|View full text |Cite
|
Sign up to set email alerts
|

A spatial-spectral classification approach of multispectral data for ground perspective materials

Abstract: A spatial-spectral classification technique for classification of materials within Hyperspectral images is described in this paper. The method considers the influence of neighboring pixels to apply local spatial context features to correctly label an unknown pixel. The spatial and spectral features are jointly applied to a Maximum Likelihood classifier that uses material class models defined by a Mixture of Gaussians to adaptively account for spectral variability and noise. Experimental results compare the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…However, hyperspectral data by itself may not provide comprehensive information of ground objects for certain applications. Previous research has shown that the spatial information can be utilized for a variety of image analysis tasks [1], [2]. In addition, LiDAR, an active optical remote sensing technique that measures the distance to an object by sending and receiving pulses from a laser, has been utilized to discriminate different ground classes with different elevations, and used for multiple applications, e.g., landscape level analysis of salt marsh plant habitats [3] and large area ecosystem characterization [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, hyperspectral data by itself may not provide comprehensive information of ground objects for certain applications. Previous research has shown that the spatial information can be utilized for a variety of image analysis tasks [1], [2]. In addition, LiDAR, an active optical remote sensing technique that measures the distance to an object by sending and receiving pulses from a laser, has been utilized to discriminate different ground classes with different elevations, and used for multiple applications, e.g., landscape level analysis of salt marsh plant habitats [3] and large area ecosystem characterization [4].…”
Section: Introductionmentioning
confidence: 99%
“…We argue that the goal of the majority of spectral imaging analysis is material classification [3,16,17]. Indeed, once the spectral datacube is reconstructed, the spectrum at each spatial location is compared to known spectra to make a classification.…”
Section: Introductionmentioning
confidence: 99%